2018
DOI: 10.1016/j.jand.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Portion Sizes from 24-Hour Dietary Recalls Differed by Sex among Those Who Selected the Same Portion Size Category on a Food Frequency Questionnaire

Abstract: These sex differences in reported 24HDR food portions-even among participants who selected the same portion size on the QFFQ-suggest that the use of methods that account for differences in the portions consumed by men and women when QFFQs are quantified may provide more accurate absolute dietary intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…The question whether diet quality is better and associations with adiposity measures are stronger among women than men is difficult to explain. Besides being a chance finding, it is possible that women report their diet more accurately or that portion sizes in the QFFQ are closer to those consumed by women than men as suggested previously [ 5 ]. Given the similar magnitude of the associations between a high quality diet and chronic disease incidence and mortality in both sexes [ 20 , 31 ], the large differences in VAT and the VAT/SAT ratio between men and women are probably due to an underlying biologic mechanism, most likely genetic variation, that leads to differential fat accumulation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The question whether diet quality is better and associations with adiposity measures are stronger among women than men is difficult to explain. Besides being a chance finding, it is possible that women report their diet more accurately or that portion sizes in the QFFQ are closer to those consumed by women than men as suggested previously [ 5 ]. Given the similar magnitude of the associations between a high quality diet and chronic disease incidence and mortality in both sexes [ 20 , 31 ], the large differences in VAT and the VAT/SAT ratio between men and women are probably due to an underlying biologic mechanism, most likely genetic variation, that leads to differential fat accumulation.…”
Section: Discussionmentioning
confidence: 93%
“…If sex differences in portion sizes and other aspects of food consumption are not accurately captured, the validity of the findings by sex are challenged [ 2 ]. A comparison of eating patterns between men and women has indicated that, in general but not for all foods, portions consumed by men were larger than those by women [ 3 – 5 ]. For food choices, differences between men and women have been reported, e.g., women eat more fruits, vegetables, cereals, milk and dairy products than men do, while men consume more meat products, eggs, alcohol, and various starchy foods than women [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study with Japanese subjects aged between 20 and 69 yrs, a significant difference in food consumption was found according to age and gender as seasoning, fish, noodle, and loaf bread were presented as a major supply source of total sodium intake [ 21 ]. In a Hawaii-Los Angeles Multiethnic Cohort study which examined sex differences in reported food portions from 24-h dietary recalls (24-h recalls) among those who selected the same portion size category on a quantitative food frequency questionnaire, mean intake amounts from 24-h recalls were significantly higher for men than for women for certain foods such as beef/lamb/veal, white rice, and lettuce/tossed salad [ 22 ]. Fourteen days of food grocery receipts were analyzed and high-income families bought more vegetables and dairy products and fewer frozen desserts and the quality of meals represented by the healthy eating index (HEI) was significantly higher than those of low-income families [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in food consumption between men and women have been recognized by several studies. Men’s food portions were larger than women’s in general, but not for all single foods or food groups compared [ 4 , 5 , 6 , 7 ]. There were also gender differences in food choices [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%